2014
DOI: 10.1158/1538-7445.am2014-3941
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3941: The Egr1 transcription factor contributes to radiation-induced apoptosis in the mouse hippocampus and intestinal crypts

Abstract: Although radiation therapy is a mainstay of cancer treatments, it can have deleterious effects on normal tissues, leading to poor quality of life for cancer survivors. Stem cells in normal tissues are particularly sensitive to radiation. It is believed that they are depleted after radiation, resulting in late sequelae such as low IQ, cognitive disorders, intestinal malabsorption, infertility, and skin injuries. Our laboratory has found that normal tissue stem cells express high levels of Early Growth Response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These findings implied that SKPs were not only resistant to UVB-induced apoptosis and DNA damage, but also greatly proliferated after UVB irradiation in this experiment, which were to some extent inconsistent with other reports. In general, it is considered that cells after UVB radiation or IR would become versiform, injured, aged, reductive, and even apoptotic [ 13 – 15 , 28 , 29 ]. This phenomenon indeed occurred in FBs in our study, indicating the obvious reduction and deformation of FBs after a certain dose of UVB radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings implied that SKPs were not only resistant to UVB-induced apoptosis and DNA damage, but also greatly proliferated after UVB irradiation in this experiment, which were to some extent inconsistent with other reports. In general, it is considered that cells after UVB radiation or IR would become versiform, injured, aged, reductive, and even apoptotic [ 13 – 15 , 28 , 29 ]. This phenomenon indeed occurred in FBs in our study, indicating the obvious reduction and deformation of FBs after a certain dose of UVB radiation.…”
Section: Resultsmentioning
confidence: 99%
“…After exposure to UV, Nrf2 translocates into the nucleus and its signaling pathway is provoked, which further activates downstream cytoprotective genes and upregulates antioxidant enzyme heme oxygenase-1 (HO-1) to resist UVB-mediated cellular injury and eventually sustains cells survival [ 11 ]. Generally, apoptosis prevails in DNA or cell damage induced by UV radiation or ionization, which leads to gH2AX phosphorylation (pH2AX, an important biomarker of DNA damage) presence, cells reduction, senescence, and death [ 12 15 ]. However, some reports indicated that after hair-follicle-bulge stem cells (SCs) or embryonic stem (ES) cells were exposed to a certain dose of ionizing radiation (IR), cells biological activity and viability were rarely affected, let alone their differentiation or senescence, the mechanism of which was associated with Bcl-2 upregulation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%